STEP for e-manufacturing: Concepts and applications - Azmi, Azwan Iskandar; Zulkifli, Abdul Nasir; Mohamed Elias, Ezanee; Daud, Ruslizam (2004)
The ISO standard, STandard for the Exchange Product Data Model or STEP is known as a standard data exchange format for design and manufacturing.STEP is intended to provide a complete representation of a product throughout the product lifecycle. More recently, with the idea of e-manufacturing is being put into great emphasis; this brings the consideration of implementing STEP into that new idea.This paper presents the concepts, applications, and perspectives of STEP in the e-manufacturing environment.The objective is to provide guidelines and references for future research and implementation related to this area.